Timur Tengah dan Ekonomi Syariah: Studi Empiris terhadap Perkembangan Ekonomi Syariah di Timur Tengah - Latifah, Nur Azizah; Jamal, Mulyono (AL-FALAH : Journal of Islamic Economics, 2019)
Purpose: This study is intended to identify how the practice and development of Islamic economics in the Middle East - the Arabian Peninsula.Design / Method / Approach : This study begins with a process of historical reading of economic activity and how the Islamic economy is the norm applied by economic institutions. In drawing conclusions, this study intensely uses historical facts as the source and foundation of conceptualization and equity of study findings.Findings : Development of a Sharia Economy in the Middle East Before the birth of the oil era at the beginning of the 20th, the main Gulf region was on the southern coast, acting as a liaison to Indian markets from the West and Somalia from the East. One of them is Aden, a natural port of Yemen, where ships from Ethiopia and India dock. The eastern path through the coast of the southern Arabian peninsula and up to the Persian bay is a link through the sea from Yemen to Iraq and transmits by land to Sham. On the track, traders crossed the Yemeni, Iraqi, Palmyra and Syrian markets. In each region they sell commodities that are not there and also buy commodities in the region to be brought to other regions. Because of a number of factors, for the time being, the economic development of the region is arguably stagnant and escaped world attention. Along with the development of science and technology in the early twentieth century, the need for fuel oil began to increase.Originality /Novelty: This article is not only a reference, but also a copy that can be used as a historical foundation to understand the development of Islamic economics in Middle Eastern friends.